Distinction between right to compensation for damages and right to the insured amount according to Mihailo Konstantinović: Classic institutes and modern law - Petrović-Tomić Nataša (Anali Pravnog Fakulteta u Beogradu)
Author arguments that the distinction between the right to compensation for damage and the right to the insured amount originates from the work of Mihailo Konstantinović. Although the Draft Law on Obligations and Contracts does not regulate all types of insurance, Konstantinović has clearly and precisely stated that "the insured amount received by the insured party from the insurance company does not replace compensation for damage to which the party is entitled, according to the general rules on compensation for damage." This wording has not lost its relevance today. Conversely, it is more relevant than ever. Based on the work of Mihailo Konstantinović, the author presents the argument that the Serbian regulatory framework is a limiting factor to the development of the insurance market. A favorable legal framework does not limit insurance according to the type of insurance, but recognizes the type of coverage and the nature of contracted obligation.